A critical review and weight of evidence approach for assessing the bioaccumulation of phenanthrene in aquatic environments. (22nd March 2021) - Armitage, James M.; Toose, Liisa; Camenzuli, Louise; Redman, Aaron D.; Parkerton, Tom F.; Saunders, David; Wheeler, James; Martin, Alberto; Vaiopoulou, Eleni; Arnot, Jon A.
Abstract: Bioaccumulation (B) assessment is challenging because there are various B‐metrics from laboratory and field studies, multiple criteria and thresholds for classifying bioaccumulative (B), very bioaccumulative (vB), and not bioaccumulative (nB) chemicals, as well as inherent variability and uncertainty in the data. These challenges can be met using a weight of evidence (WoE) approach. The Bioaccumulation Assessment Tool (BAT) provides a transparent WoE assessment framework that follows Organisation for Economic Co‐operation and Development (OECD) principles for performing a WoE analysis. The BAT guides an evaluator through the process of data collection, generation, evaluation, and integration of various lines of evidence (LoE) (i.e., B‐metrics) to inform decision‐making. Phenanthrene (PHE) is a naturally occurring chemical for which extensive B and toxicokinetics data are available. A B assessment for PHE using the BAT is described that includes a critical evaluation of 74 measured in vivo LoE for fish and invertebrate species from laboratory and field studies. The number of LoE are reasonably well balanced across taxa (i.e., fish and invertebrates) and the different B‐metrics. Additionally, in silico and in vitro biotransformation rate estimates and corresponding model‐predicted B‐metrics are included as corroborating evidence. Application of the BAT provides a consistent, coherent, and scientifically defensible WoE evaluation to conclude that PHE is not bioaccumulative (nB) because the overwhelming majority of the bioconcentration, bioaccumulation, and biomagnification metrics for both fish and invertebrates are below regulatory thresholds. An analysis of the relevant data using fugacity ratios is also provided, showing that PHE does not biomagnify in aquatic food webs. The critical review identifies recommendations to increase the consistency of B assessments, such as improved standardization of B testing guidelines, data reporting requirements for invertebrate studies, and consideration of temperature and salinity effects on certain B‐metrics. Integr Environ Assess Manag 2021;17:911–925. © 2021 Concawe. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC) KEY POINTS: The Bioaccumulation Assessment Tool (BAT) provides a transparent framework that follows Organisation for Economic Co‐operation and Development (OECD) principles for performing a weight of evidence approach. A critical review of bioaccumulation and toxicokinetic data for phenanthrene is described that includes a critical evaluation of 74 measurements in fish and invertebrate species from laboratory and field studies. The overwhelming majority of bioaccumulation metrics are below regulatory thresholds. Recommendations to improve the consistency of bioaccumulation assessments are provided.